Effects of Zinc Oxide Nanoparticles Synthesized Using Aspergillus niger on Carbapenem-Resistant Klebsiella pneumonia In Vitro and In Vivo - Rasha, Elsayim; Alkhulaifi, Manal M.; AlOthman, Monerah; Khalid, Ibrahim; Doaa, Elnagar; Alaa, Khatab; Awad, Manal A.; Abdalla, Mohnad (Frontiers in Cellular and Infection Microbiology, 2021)
Currently, the mortality rate in Saudi Arabia’s ICUs is increasing due to the spread of Klebsiella pneumoniae carbapenemase (KPC)-producing bacteria. This study was carried out to evaluate the ability of biologically synthesized zinc oxide nanoparticles (ZnO-NPs) using Aspergillus niger to overcome carbapenem-resistant K. pneumoniae (KPC) in vitro and in vivo. ZnO-NPs were synthesized via a biological method and characterized using UV–Vis spectroscopy, Zetasizer and zeta potential analyses, x-ray diffraction spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy (SEM), and energy-dispersive x-ray spectroscopy (EDX). In vitro sensitivity of KPC to ZnO-NPs was identified using the well diffusion method. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by a macro-dilution method. The morphological alteration of KPC cells after ZnO-NPs treatment was observed by SEM. The in vivo susceptibility of KPC cells to ZnO-NPs ointment was evaluated using wound healing in experimental rats. The chemical characterization findings showed the formation, stability, shape, and size of the synthesized nanoparticles. The MIC and MBC were 0.7 and 1.8 mg/ml, respectively. The in vivo results displayed reduced inflammation and wound re-epithelialization of KPC-infected rats. These findings demonstrated that ZnO-NPs have great potential to be developed as antibacterial agents.